Temporal Trends in Incidence and Outcomes of Peripartum Cardiomyopathy in the United States: A Nationwide Population‐Based Study. Issue 3 (4th June 2014) - Kolte, Dhaval; Khera, Sahil; Aronow, Wilbert S.; Palaniswamy, Chandrasekar; Mujib, Marjan; Ahn, Chul; Jain, Diwakar; Gass, Alan; Ahmed, Ali; Panza, Julio A.; Fonarow, Gregg C.
Abstract : Background: The reported incidence of peripartum cardiomyopathy (PPCM) in the United States varies widely. Furthermore, limited information is available on the temporal trends in incidence and outcomes of PPCM. Methods and Results: We queried the 2004‐2011 Nationwide Inpatient Sample databases to identify all women aged 15 to 54 years with the diagnosis of PPCM. Temporal trends in incidence (per 10 000 live births), maternal major adverse events (MAE; defined as in‐hospital mortality, cardiac arrest, heart transplant, mechanical circulatory support, acute pulmonary edema, thromboembolism, or implantable cardioverter defibrillator/permanent pacemaker implantation), cardiogenic shock, and mean length of stay were analyzed. From 2004 to 2011, we identified 34 219 women aged 15 to 54 years with PPCM. The overall PPCM rate was 10.3 per 10 000 (or 1 in 968) live births. PPCM incidence increased from 8.5 to 11.8 per 10 000 live births ( P trend <0.001) over the past 8 years. MAE occurred in 13.5% of patients. There was no temporal change in MAE rate, except a small increase in in‐hospital mortality and mechanical circulatory support ( P trend <0.05). Cardiogenic shock increased from 1.0% in 2004 to 4.0% in 2011 ( P trend <0.001). Mean length of stay decreased during the study period. Conclusion: From 2004 to 2011, the incidence of PPCM has increased in the United States. Maternal MAE rates overall have remained unchanged while cardiogenic shock, utilization of mechanical circulatory support, and in‐hospital mortality have increased during the study period. Further study of the mechanisms underlying these adverse trends in the incidence and outcomes of PPCM are warranted.